HUBUNGAN SCREEN TIME DENGAN KEMAMPUAN MOTORIK SISWA SMP FASE D - Syahada Tamyatul Jannah; Aan Fardani Ubaidillah; Rahmad Rusminto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information technology has driven behavioral changes among secondary school students, particularly regarding the duration of digital device use or screen time. High screen time intensity potentially displaces physical activity time, which plays a crucial role in motor skill development. This study aimed to examine the relationship between screen time and motor skills of junior high school students in Phase D. A quantitative approach with a correlational design was employed. Subjects consisted of 60 seventh and eighth-grade students selected through proportionate stratified random sampling. Data were collected using a screen time questionnaire covering daily duration, usage time patterns, and types of digital activities, as well as the Barrow Motor Ability Test comprising standing broad jump, zig-zag run, and medicine ball put. Data analysis included normality tests, independent samples t-test, and Pearson correlation. Results showed that screen time was significantly and negatively correlated with standing broad jump (r = −0.672; p = 0.000) and medicine ball put (r = −0.558; p = 0.000), and positively correlated with zig-zag run time (r = 0.614; p = 0.000). The mean daily screen time of 4.62 hours/day exceeded the WHO recommendation of 2 hours/day. Significant differences in motor abilities were found based on sex. These findings imply the need for digital literacy integration in physical education and school-based motor intervention programs.